FORMULASI SEDIAAN TABLET KUNYAH DARI EKSTRAK ETANOL CABAI RAWIT (Capsicum frutescens L.) DENGAN VARIASI PENGISI MANITOL SUKROSA MENGGUNAKAN METODE GRANULASI BASAH - ., Friska Iga Setiadefi (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Cabai rawit (Capsicum frutescens L.) is one of medicinal plants that containsantioxidant activity. Cabai rawit were made into chewable tablet to improve thetaste from pungency with the sweetener, and also to simplified the administrationof active contents from cabai rawit. The purpose of this research was to formulate atablet from fruit extract of cabai rawit and used combination of filler that couldaffect the physical characteristics of chewable tablet. Chewable tablets were madeinto three formulas used combination of mannitol-sucrose with certain ratio, FI(80:20%), FII (50:50%), and FIII (20:80%). Extracts were made with maserationmethod and the manufacture of chewable tablet used wet granulation method.Granules from the wet granulation were evaluated with several evaluation such asflow properties, and particles size distribution. Granules that had qualified thenwere compressed as chewable tablet and also got psychical characteristicsevaluation such as physical appearance, size uniformity, weight uniformity,hardness test, friability, disintegration time and taste response test. All of theformulas were qualified compared to tablet standard in literature. The best result ofphysical evaluation was FII with angle of repose 26,04°; 5,38 kg of hardness test,0,9% of friability test and 7,27 minutes of desintegration time. Keywords : chewable tablet, cabai rawit (Capsicum frutescens L.), mannitol, sucrose, wet granulation